2013
DOI: 10.1186/1472-6831-13-15
|View full text |Cite
|
Sign up to set email alerts
|

Weight, height and eruption times of permanent teeth of children aged 4–15 years in Kampala, Uganda

Abstract: BackgroundTooth eruption is a continuous biological process by which developing teeth emerge through the jaws and the overlying mucosa to enter into the oral cavity. Tooth eruption time and sequence are important factors in dental treatment planning, particularly in orthodontics, but also in forensic dentistry to estimate age of a child. Tooth eruption time is influenced by many factors. In this study we set out to determine the timing of eruption of permanent teeth and assess its association with the height a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 22 publications
8
58
0
5
Order By: Relevance
“…Generally, the mean eruption time for female infants was less than that of the male ones. Agarwal et al (19) found that for the same age group, males had late dental eruption, in support of the earlier findings (20).…”
Section: Discussionsupporting
confidence: 59%
“…Generally, the mean eruption time for female infants was less than that of the male ones. Agarwal et al (19) found that for the same age group, males had late dental eruption, in support of the earlier findings (20).…”
Section: Discussionsupporting
confidence: 59%
“…Table 1 summarizes ages at the end of the first and second phases of the mixed dentition in different populations. The largest difference in the ending of both the first and second phase of mixed dentition was between Ugandan 6 and Iranian 7 girls, 1.6 and 1.7 years, respectively. Permanent teeth have been noticed to erupt earlier in African children than in those of white origin.…”
Section: Introductionmentioning
confidence: 91%
“…23 However, our results are consistent with the study carried out by Kutesa et al (2013), who found no significant differences in the eruption times between teeth in the right and left side of the jaw. 1 In our study, age of study population ranged from 5 -15 years, of which 8-11 years was the most frequent range in age group. Age of subjects of present study is consistent with previous study reported by Dahiya .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Exfoliation of primary teeth and in turn the eruption of new teeth, is a constant age-related progression by which the teeth arise through the upper and lower jaws and the overlaying mucosa to enter into the oral cavity and in turn occlude with the teeth of the opposite arch. [1][2][3] The permanent teeth usually emerge between the ages of 6 -14 years, not including the 3rd molars that usually are seen emerging at the ages of 17-21 years. 4,5 As teeth are the most stable structures in the human body, it can be of paramount importance in forensic medicine where estimation of age is usually required for criminal investigations and also in persons who do not have proper birth certificates whether above or below 18 years of age.…”
Section: Introductionmentioning
confidence: 99%